Fairy Tales As A Character Internalization Media In Early Children - Irwan Satria; Asiyah Asiyah (Jurnal Ilmiah POTENSIA, 2020)
Fairy tales as a medium for internalizing characters in early childhood. The purpose of. This study is to determine whether or not the influence of fairy tales as medium for character planting in early childhood. The fairy tale itself is a story did not really happen or was an imaginary story, and development of characters was a gift an education that forms the character or character that distinguishes a person from another. The samples taken were group A-2 Kindergarten Permata Bunda in Bengkulu City, with a total of 15 children aged 2.5 - 3.5 years. Method used is a type of qualitative research, with observation and data sources Interview. The results of the research obtained are fairy tales as a medium for internalizing character is very effective to be applied to early childhood and the need for habituation as well a good example to develop character from children